Die urbane Mobilitätswende messbar machen? Konzeption und Anwendung eines Mobilitätswendeindex am Beispiel der Städte Darmstadt, Frankfurt und Wiesbaden - Julius Bücher; Johannes Aertker; Christian Neumann; Thomas Klinger; Martin Lanzendorf (Raumforschung und Raumordnung)
This paper discusses an index based on the concept of mobility cultures for measuring the socio-ecological transformation of urban mobility, also referred to as the mobility transition. This index, termed the Mobility Transition Index, aims to enable municipal policymakers and planners to quantitatively assess progress in implementing the mobility transition. The uniqueness of the index lies in the consideration of both objective and subjective data, as well as the goal of incorporating as many open data sources as possible. In workshops with local experts of statistics and transport planning, the indicator set was discussed in terms of its applicability and the availability of additional data. Finally, a set of 78 measurement indicators and 16 core indicators for calculating the Mobility Transition Index emerged. Next, the index was calculated for three cities (Darmstadt, Frankfurt am Main, Wiesbaden), and discussed with experts again. The results demonstrate the potential of the index for analysing changes in urban mobility cultures. Furthermore, we identified a predominance of data related to the built environment and travel behaviour, but a lack of data for transport policy and planning, as well as for discourses and communication. We concluded that additionally to the necessity for collecting such data more extensively, a need arises for the critical examination of existing datasets and their contribution for the urban transformation of transport.